Frequency of Left Ventricular Systolic Dysfunction in Patients with Unstable Angina - mran Ellahi Soomro, Qurban Ali Rahu, Khalid Naseeb (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2014)
Objective: To determine the frequency of left ventricular systolic dysfunction (LVSD) in patients with unstable angina (UA). Study design: Cross-sectional study. Place & Duration: North ward of NICVD Karachi for six months from January to June 2014. Material & Methods: A total of 113 cases were collected from all medical wards having history of first time unstable angina. After informed consent echocardiogram was done, the severity of left ventricular systolic dysfunction was determined on basis of ejection fraction. All the information was entered in a proforma designed for the study. Results: Among 113 cases 65 (57.5%) were males. 52 (46%) patients had duration of symptoms of < 24 hours, 46 (40.7%) patients had symptoms on exertion, 48 (42.5%) patients had left ventricular dysfunction and 65 (57.5%) patients had normal left ventricular function (p=0.091). 23 (20.4%) patients had mild LV dysfunction, 14 (12.4%) had moderate LV dysfunction and 11 (9.7%) [8 males & 3 females] had severe LV dysfunction (p=0.380) Conclusion: Less than half of study population had left ventricular systolic dysfunction. Preinfarction diagnosis of LVSD will help in the management of cases who will develop myocardial infarction.